Implicações da interação genótipos x ambientes na seleção de clones de eucalipto em altitudes contrastantes - Reis, Márcio de Souza (2020)
The genotype x environment (G x E) interaction is a prevalent phenomenon that can make breeding and recommending cultivars very difficult. However, this interaction can also be considered an opportunity for gain. Thus, breeding programs must evaluate genotypes in many locations and with edaphoclimatic diversity, for a better selection and recommendation of superior genotypes. This work was conducted to study the interaction between genotypes and environments in areas with contrasting altitudes property of the Cenibra company, to recommend Eucalypitus grandis x Eucalyptitus urophylla hybrid clones based on productivity, stability, and adaptability. We evaluated 46 clones, at 36 and 72 months of age, belonging to the Cenibra breeding program, located in eastern Minas Gerais, Brazil. The experiments were installed at four different locations, two at high altitude (> 1000 m) and two at low altitude (<350 m), in a complete randomized block design, with five replicates of five plants per plot. The clones were evaluated for diameter at breast height (DBH) and plant height, allowing the estimate of commercial volume with bark. Once the assumption of homogeneity of the residual variance was observed, we performed the joint analysis of the experiments, verifying the effects of the site and the interaction of the genotypes with the sites. The genetic parameters were estimated, proving the variability between the clones and the significant productivity gains with the selection. The interaction was significant between the high and low altitude regions. Within each altitude class, the high region (Sabinópolis and Cocais) showed low G x E interaction. In contrast, in the environments of the low region (Belo Oriente and Pingo d`Água) there was a median G x E interaction. The high region showed higher productivity compared to the low region.